Individual and socio-cultural contexts of infertility: some experiences among women in Chandigarh, India - Kumar, Dinesh; Navya; Kumar, Manoj (International Journal Of Community Medicine And Public Health, 2025)
Background: Infertility has emerged as one of the most challenging reproductive health issues of modern times affecting approximately 10–15% of couples globally. Infertility is a multidimensional issue requiring psychosocial interventions. To explore perceptions regarding individual, psychosocial and cultural influences on infertility among women of reproductive age in Chandigarh. To interrelate individual, psychosocial and cultural influences of infertility with demographic characteristics of women. Methods: Cross-sectional study conducted during January 2025 to June 2025, using mixed-method approach included 256 women aged 18–49 years in Chandigarh selected by stratified two-stage random sampling technique. They were interviewed in depth for their opinions concerning individual and socio-cultural contexts of infertility. Quantitative analysis included descriptive statistics and Chi-square tests. Results: Most participants were aged 26–35 years (42.6%), followed by 36–49 years (41.8%), Blaming women for infertility was reported by 83 (32.4%) respondents. Infertility was perceived influencing adversely women’s self-esteem strongly agreed by 58 (22.7%) respondents, Societal attitudes included banning from social functions (22.3%), lack of respect from family (149.2%), extramarital affairs (16.4%). Cultural beliefs included emotional breakdown (33.6%) followed by old age support (8.8%). No significant associations between socio-cultural contexts and demographic characteristics were found, indicating that stigma and negative perceptions surrounding infertility cut across all socio-demographic groups. Conclusions: Infertility was mostly attributed to women with significant emotional, social and cultural linkages such as guilt, reduced self-esteem, lack of family support and exclusion from social functions. Individual and socio-cultural contexts were found irrespective of demographic characteristics. Psycho-social interventions along with medical infertility management strategies should be adopted addressing stigma and cultural misconceptions.